ANALISIS TINGKAT KESEJAHTERAAN MASYARAKAT NELAYAN MUARA SEMBILANG KABUPATEN KUTAI KARTANEGARA - Fikriani, Nuvia; Sugiharto, Eko; Fahrizal, Wahyu (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
The study was purpose to determine the characteristics of fisherman’s, exchange rate fisherman’s Muara Sembilang and to determine welfare level receipts of government assictance due to Covid-19 Pandemic. The research was carried out from April 2022 to June 2022 in Muara Sembilang, Kutai Kartanegara Regency. The sampling method used purposive sampling with the number of respondents as many as 40 respondents. Methods of data analysis using descriptive analysis, exchange rate fisherman’s analysis and indicator welfare BPS 2014 for receiepts Program Keluarga Harapan. The results showed that the characteristics of fisherman’s are around 42 to 46 aged with education average elementary school and have dependents of family as much as two person, majority of religion are moeslim and most of the etnic group are Buginese. Beside that, the result show that in 2021 exchage rate fisherman’s in the amount of 1,26 for houlsehold income and exchange rate fisherman’s in the amount of 2,06 for fishery income. The result of exchange rate fisherman’s indicated that welfare level are good. Receiepts program Keluarga Harapan in Muara Sembilang Samboja Subdisrict, Kutai Kartanegara Regency indicated in underprosperous category. Keywords : Fisherman’s, Fisherman’s Exchange Rate, Program Keluarga Harapan